1998
DOI: 10.1021/bk-1998-0677.ch018
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Calculations for Kinetic Modeling of Halocarbons

Abstract: The thermochemistry and reaction kinetics of halogenated hydrocarbons have been investigated by ab initio methods in order to improve our understanding of their flame chemistry and likely roles in flame suppression. Bond additivity corrections at the G2, G2(MP2), CBS-4 and CBS-Q levels of theory were developed for fluorinated and chlorinated C 1 and C 2 species, including saturated and unsaturated compounds. The resulting enthalpies of formation are in excellent agreement with experimental values. Transition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Haworth et al published a study on more than one hundred fluorinated C1 and C2 hydrofluorocarbon and oxidized hydrofluorocarbon molecules; both stable molecules and radicals. Berry et al , reported the negative errors in the calculated enthalpies by atomization; where the errors observed were linearly dependent upon the number of C–F bonds in the molecule. Wang et al , re-evaluated the enthalpy of formation of fluorinated hydrocarbons and also determined enthalpy of formation of fluorinated methyl peroxides using isodesmic work reactions with re-evaluated species.…”
Section: Introductionmentioning
confidence: 99%
“…Haworth et al published a study on more than one hundred fluorinated C1 and C2 hydrofluorocarbon and oxidized hydrofluorocarbon molecules; both stable molecules and radicals. Berry et al , reported the negative errors in the calculated enthalpies by atomization; where the errors observed were linearly dependent upon the number of C–F bonds in the molecule. Wang et al , re-evaluated the enthalpy of formation of fluorinated hydrocarbons and also determined enthalpy of formation of fluorinated methyl peroxides using isodesmic work reactions with re-evaluated species.…”
Section: Introductionmentioning
confidence: 99%
“…Berry et al 71,72 applied various composite protocols and also the BAC-MP4 method to calculate heats of formation for fluoroethanes. The G2, G2(MP2), CBS-4, and CBS-Q model chemistries along with their bond additivity counterparts were invoked in these studies.…”
mentioning
confidence: 99%